Electrical conductivity, Seebeck coefficient and optical properties of SnO2 film deposited on ITO by dip coating - Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2009)
Electrical and optical properties of SnO2 film deposited on indium tin oxide substrate by dip coating have been investigated. The electrical conductivity of the SnO2 film exhibits the extrinsic conductivity mechanism with two shallow and deep donor levels. The current voltage characteristics of SnO2 film confirm the presence of space charge limited conduction. The density of states at the Fermi level N(E-F) for the SnO2 film was determined using current-voltage characteristics and was found to be 1.63 x 1016 eV(-1) m(-3). The Seebeck coefficient of the SnO2 at room temperature indicates the n-type electrical conductivity. The Seebeck coefficient suggests that the electrical conductivity of the SnO2 film varies from n-type conductivity to p-type conductivity with increasing temperature. The optical constants, such refractive index as dielectric constants, were determined from the reflectance, transmittance and absorption spectra. The refractive index dispersion behavior of the SnO2 film obeys the single oscillator model. The fundamental absorption edge in SnO2 film is formed by the direct allowed transitions with band gap of 3.40 eV. C 2008 Elsevier B.V. All rights reserved.
Keywords: Electronic transport; Semiconductors